Time Synchronized High Performing Cluster-Based Routing Algorithm for Wireless Sensor Networks - DENG, Huifang (Information Management and Business Review, 2013)
In this paper, we investigated the data fusion routing algorithm and the time synchronization algorithm for the wireless sensor networks. First, we proposed a new data fusion routing algorithm - Low Energy Consumption Cluster-Based Routing Algorithm (LECCBRA). Simulation results show that the total energy can be effectively saved, and the balance in energy consumption between clusters can be achieved with LECCBRA, thus the network lifetime is extended. Second, we proposed a time synchronization algorithm - Clustering-based Time Synchronization (CBTS), which is suitable for LECCBRA. Performance analysis and simulation results show that the total energy can be effectively saved, and the accuracy can be improved.